Bonding Primary Aircraft Structure The Issues. (Manufacturing Engineering)
Mechanical fasteners, which require holemaking and installation operations on the floor, are the primary means of assembling aerospace products. Bonded joints in aerospace structures have the potential for significant performance and service advantages over traditionally fastened structures.